2008
DOI: 10.1016/j.ejvs.2008.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Fistula Formation using Transposed Basilic Vein: Extensive Single Centre Experience

Abstract: BBAVF represents an important option for vascular access with acceptable patency rates, although complication rates remain significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 22 publications
(23 reference statements)
5
37
0
Order By: Relevance
“…To date, limited and conflicting data exist regarding primary failure and the patency rates of one-stage and two-stage procedures. [4][5][6][7][8][9][10][11][12] Each procedure has advantages and disadvantages. The one-stage procedure offers the benefits of a single operation with earlier functional patency and possible shorter duration with a central venous catheter.…”
mentioning
confidence: 99%
“…To date, limited and conflicting data exist regarding primary failure and the patency rates of one-stage and two-stage procedures. [4][5][6][7][8][9][10][11][12] Each procedure has advantages and disadvantages. The one-stage procedure offers the benefits of a single operation with earlier functional patency and possible shorter duration with a central venous catheter.…”
mentioning
confidence: 99%
“…87.6). 12,[16][17][18][19] In comparison with brachiocephalic fistulas, brachiobasilic AV fistulas are more likely to mature, although they are more susceptible to late thrombosis. However, a randomized study showed similar patencies of brachiocephalic and brachiobasilic AV fistulas.…”
Section: Nonautogenous Prosthetic Vascular Accessmentioning
confidence: 97%
“…Primary patency for BBAVFs at one year of 72% (range, 23-90%) and at two years of 62% (11-86%) have been quoted. 12,13 These favourable results, coupled with increasing enthusiasm for minimally invasive methods, have generated interest in novel approaches for VAS. Similar methods have been used extensively for harvesting of the saphenous vein in coronary artery bypass grafting.…”
Section: Discussionmentioning
confidence: 99%
“…16 Reported prevalence of complications for BBAVF remains very high (≥71%). 13,22,23 These complications include large haematomas necessitating surgical evacuation, seromas and wound infection, often resulting from this invasive approach. However, these complications appear to be self-limiting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation